2019
DOI: 10.1002/jum.15118
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Contrast‐Enhanced Ultrasound for Early Therapeutic Evaluation of Hepatocellular Carcinoma After Transcatheter Arterial Chemoembolization

Abstract: Objectives We aimed to investigate whether contrast‐enhanced ultrasound (CEUS) could be useful for early evaluation of the treatment response to transcatheter arterial chemoembolization (TACE) of hepatocellular carcinoma (HCC). Methods This study retrospectively selected HCCs in which homogeneous retention of iodized oil was confirmed on non–contrast‐enhanced computed tomography performed immediately after TACE. Therapeutic responses of HCCs were evaluated by CEUS 1 to 2 days after TACE and by contrast‐enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…The results also showed that lesion diameter was an independent risk factor for poor TR after TACE. Watanabe et al found that tumour size was a risk factor for poor prognosis, consistent with our results [ 30 32 ], and diameter reflects tumour progression. Tumours with larger diameters are more progressive and invasive than those with smaller diameters.…”
Section: Discussionsupporting
confidence: 93%
“…The results also showed that lesion diameter was an independent risk factor for poor TR after TACE. Watanabe et al found that tumour size was a risk factor for poor prognosis, consistent with our results [ 30 32 ], and diameter reflects tumour progression. Tumours with larger diameters are more progressive and invasive than those with smaller diameters.…”
Section: Discussionsupporting
confidence: 93%
“…Due to population, intervention, comparison, outcomes and study design (PICOS) not meeting the inclusion criteria, 4095 studies were further excluded (figure 1). Finally, 36 studies involving 5843 patients were included in the meta-analysis 11–14 16 18 20–22 24 34–39. The completed search strategy is in online supplemental file 1.…”
Section: Resultsmentioning
confidence: 99%
“… 17 Previous studies have indicated that CEUS is comparable to CT/MRI in evaluating percutaneous ablation treatment 10 , 18–20 and TACE. 21 , 22 However, CEUS may have different imaging features compared with CT/MRI owing to the different contrast mediums. Whether the CT/MRI LI-RADS TRA categories and features are suitable for CEUS has not been explored yet.…”
Section: Discussionmentioning
confidence: 99%